2011
DOI: 10.3109/17435390.2011.569096
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the calibrated thrombin generation test (cTGT) as the reference assay to evaluate the procoagulant activity of nanomaterials

Abstract: We validated a preclinical toxicological screening assay and provided guidelines to evaluate the potential impact of nanoparticles (NPs) on blood coagulation. Five NPs with various physicochemical properties were studied using several existing methods of clotting times and thrombin generation assays in human normal pool plasma. In both recalcification clotting time (RCT) and calibrated thrombin generation test (cTGT), the NPs exhibited procoagulant activity (SiO₂ ≥ SiC ≥ TiC > CuO > CB) but cTGT was more sensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 52 publications
2
25
0
Order By: Relevance
“…Activation and cleavage of mouse plasma kallikrein by superparamagnetic iron oxide nanoparticles in vitro was shown to be related to kallikrein activation in vivo [90]. A study of five nanomaterials (carbon black, silicon dioxide, silicon carbide, titanium carbide and copper oxide) for which various degrees of thrombogenicity had been demonstrated in vivo by previous studies revealed corresponding procoagulant activity in vitro in APTT and calibrated thrombin generation assays [91]. This study also concluded that although both assays detected procoagulant activity of the tested nanomaterials, the calibrated thrombin generation assay appeared to be more sensitive [91].…”
Section: Assays With “Fair” In Vitro-in Vivo Correlationmentioning
confidence: 99%
“…Activation and cleavage of mouse plasma kallikrein by superparamagnetic iron oxide nanoparticles in vitro was shown to be related to kallikrein activation in vivo [90]. A study of five nanomaterials (carbon black, silicon dioxide, silicon carbide, titanium carbide and copper oxide) for which various degrees of thrombogenicity had been demonstrated in vivo by previous studies revealed corresponding procoagulant activity in vitro in APTT and calibrated thrombin generation assays [91]. This study also concluded that although both assays detected procoagulant activity of the tested nanomaterials, the calibrated thrombin generation assay appeared to be more sensitive [91].…”
Section: Assays With “Fair” In Vitro-in Vivo Correlationmentioning
confidence: 99%
“…Consequently, these NPs did not prevent the formation of a solid fibrin scaffold as observed with the control. As demonstrated in previous studies, SiO 2 and Ag NPs are also procoagulants (Laloy et al 2012(Laloy et al , 2014a. One potential hypothesis of the underlying mechanism is that the charges of SiO 2 and Ag NPs induce a catalytic surface for coagulation and fibrinolytic factors, disturbing the hemostatic balance.…”
Section: Discussionmentioning
confidence: 73%
“…A spectrophotometric (890 nm) microtiter plate reader measures the optical density changes in euglobulin clot of plasma over time. It is known that NPs interfere with methods using light absorbance detection (Laloy et al 2012). Although ECLT is based on an optical density, there is no light interference with this assay.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations